Phytochemical profiling of Clusia valerioi (Standl.) floral resin and Its correlation with the chemical composition of propolis from southern Costa Rica - Segura-Víquez, Andrea (2025)
Fil: Segura-Víquez, Andrea. Universidad Nacional de Costa Rica. Facultad de Ciencias Exactas y Naturales. Escuela de Química. Laboratorio de Productos Naturales y Ensayos Biológicos; Costa Rica.